Forgotten Livelihood Heritage: An Uncertainty Identity-Theory Analysis of the Re(de)generation Process Among Floating Market Traders' Children in South Kalimantan - Fitriyana, Amalia; Awwalin, Ellya Nur; Salma, Nur Zahidatus; Shadiqi, Muhammad Abdan; Putri, Zerlinda Rezkika Lestari (Faculty of Psychology, Universitas Gadjah Mada, 2024)
The floating markets of South Kalimantan, a vital piece of cultural heritage and economic icon, are at risk of extinction due to modernization and the declining interest of the Gen Z children of acil jukung (floating market traders) in continuing the tradition. This research addresses the critical issue of regeneration barriers through the lens of uncertainty-identity theory, exploring why younger generations are reluctant to sustain this livelihood. Using a qualitative case study approach, data were collected through observations, semi-structured interviews, and focus group discussions with nine Gen Z participants (six female and three male) from the Lok Baintan and Muara Kuin floating markets. The findings identify three primary obstacles: income uncertainty, environmental unpredictability, and a perceived mismatch between the profession and Gen Z's aspirations, often accompanied by feelings of shame. Despite these challenges, participants expressed pride in their parents' roles and proposed innovations, such as diversifying merchandise, enhancing boat aesthetics, utilizing social media for promotion, and forming a community of traders. This study highlights the psychological and social dynamics behind regeneration challenges while offering actionable strategies to preserve the cultural and economic sustainability of floating markets.